(untitled) (Scottish Historical and Archaeological Internet Reports, 2010)
Excavations in summer 2005 to the north of Oldmeldrum, Aberdeenshire (NGR: NJ 806 279), revealed the remains of at least three Bronze Age ring-ditch roundhouses and associated features, together apparently forming elements of an area of open settlement. The excavations were conducted in advance of the construction of a new bypass road around the north of Oldmeldrum, related to new housing development.